Dynamic output feedback control for a walking assistance training robot to handle shifts in the center of gravity and time-varying arm of force in omniwheel. (7th January 2020) - Chang, Hongbin; Wang, Shuoyu; Sun, Ping
In this study, we designed a dynamic output feedback control for a walking assistance training robot. The proposed system addresses the problems of shifts in the center of gravity and vibration associated with time-varying arm of force in omniwheel to improve the accuracy of the trajectory tracking of the walking assistance training robot. The dynamic output feedback controller was developed by constructing a velocity observer on a stochastic dynamic model of the walking assistance training robot via integration with a Lyapunov function. An analysis of the time-varying arm of force in omniwheel revealed that it increased the accuracy of the walking assistance training robot dynamic model. Thus, an adaptive law was designed such that the vibration caused by the time-varying arm of force in omniwheel was eliminated. The mean absolute practical stability in the position and velocity tracking errors was verified based on Young's inequality and stochastic stability theory. The simulation results show that the walking assistance training robot with the shifts in the center of gravity was able to track a designed trajectory and that the application of the adaptive law effectively eliminates the vibrations caused by the time-varying arm of force in omniwheel.